DESCRIPTION OF POST-TRAUMATIC STRESS DISORDER IN TSUNAMI NATURAL DISASTER VICTIMS IN ASIA: A SCOPING REVIEW - Lintang Arum, Silviana; Nur Alfian, Ilham; Putri Pijar, Briliani; Rahma Pratiwi, Aida (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to provide an in-depth understanding of the psychological impact of tsunamis, particularly focusing on Post-Traumatic Stress Disorder (PTSD), and to assist in developing effective interventions to support mental recovery for disaster victims. Method: A scoping review methodology was employed to examine the literature on PTSD caused by tsunamis in Asia. Relevant studies were identified through the Web of Science database using the keywords "PTSD AND Tsunami" and "Post Traumatic Stress Disorder." Results: The synthesis revealed the prevalence and symptoms of PTSD among tsunami survivors, as well as the risk and protective factors influencing its development. Key risk factors included the loss of family members or close friends, feelings of helplessness during the disaster, and the quality of post-disaster social support. Novelty: This article highlights the specific psychological challenges faced by tsunami survivors in Asia, particularly following catastrophic events such as the 2004 Indian Ocean tsunami. It emphasizes the need for targeted mental health interventions and contributes valuable insights for enhancing recovery efforts in disaster-prone regions.